2016
DOI: 10.18174/390435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nutritional interventions with quercetin, oat hulls, β-glucans, lysozyme, and fish oil on immune competence related parameters of adult broiler

Abstract: 2015. Effect of nutritional interventions with quercetin, oat hulls, β-glucans, lysozyme or fish oil on immune competence related parameters of adult broilers. Wageningen Livestock Research Report 977.The purpose of this experiment was to evaluate the effects of five nutritional interventions, provided during d 14 -28, including inclusion of a plant extract (quercetin); an insoluble fiber (oat hulls); a prebiotic (β-glucan); an anti-microbial protein (lysozyme), and ω-3 fatty acids from fish oil, on growth per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 149 publications
(176 reference statements)
0
3
0
Order By: Relevance
“…Goliomytis et al [ 12 ] reported that feeding broiler chicks with 0.5 or 1.0 g/kg quercetin dihydrate compound containing diet had no effects on the BWG and FI, but increased FCR. In addition, many studies have reported that the growth performance was not affected in broiler chicks fed with a chemically synthesized quercetin containing diet [ 13 , 14 , 16 , 22 ]. Conversely, Abid et al [ 18 ] reported that supplementing 0.1, 0.2, or 0.3 g/kg quercetin extracted from the locust tree to the diet of broiler chicks had positive effects on the growth performance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Goliomytis et al [ 12 ] reported that feeding broiler chicks with 0.5 or 1.0 g/kg quercetin dihydrate compound containing diet had no effects on the BWG and FI, but increased FCR. In addition, many studies have reported that the growth performance was not affected in broiler chicks fed with a chemically synthesized quercetin containing diet [ 13 , 14 , 16 , 22 ]. Conversely, Abid et al [ 18 ] reported that supplementing 0.1, 0.2, or 0.3 g/kg quercetin extracted from the locust tree to the diet of broiler chicks had positive effects on the growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…The bursa of fabricius is the important immune organ in broiler chicks [ 13 ]. Reduced weight of the immune organs represents immunosuppression, while an increase in the weight of immune organs is a manifestation of the enhancement of immunity [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation